The erythrocyte as instigator of inflammation. Generation of amidated C3 by erythrocyte adenosine deaminase. - Hostetter, M K (1989)
Myocardial ischemia is characterized by the liberation of adenosine and by complement-mediated inflammation. We have reported that amidated C3, formed when ammonia (NH3) disrupts the thiolester bond of C3, serves as an alternative pathway convertase, generates C5b-9, and stimulates phagocytic oxidative metabolism. We investigated whether the deamination of adenosine by adenosine deaminase in hematopoietic cells might liberate sufficient ammonia to form amidated C3 and thereby trigger complement-mediated inflammation at ischemic sites. In the presence of 4 mM adenosine, NH3 production per erythrocyte (RBC) was equal to that per neutrophil (PMN) (3.3 X 10(-15) mol/cell per h). Because RBC outnumber PMN in normal blood by a thousandfold, RBC are the major source of NH3 production in the presence of adenosine. NH3 production derived only from the deamination of adenosine by the enzyme adenosine deaminase and was abolished by 0.4 microM 2'-deoxycoformycin, a specific inhibitor of adenosine deaminase. When purified human C3 was incubated with 5 X 10(8) human RBC in the presence of adenosine, disruption of the C3 thiolester increased more than twofold over that measured in C3 incubated with buffer, or in C3 incubated with RBC (P less than 0.05). The formation of amidated C3 was abolished by the preincubation of RBC with 2'-deoxycoformycin (P less than 0.001). Amidated C3 elicited statistically significant release of superoxide, myeloperoxidase, and lactoferrin from PMN. Thus, the formation of amidated C3 by RBC deamination of adenosine triggers a cascade of complement-mediated inflammatory reactions.